The Labour Relations and the Canadian Charter; the aftermath of the first decisions - Cantin, J. (Revue générale de droit, 1988)
The Charter was introduced at a time when there was no real demand for its existence. In this article, the author reviews the origin of the Charter and examines the impact on labour law of the initial decisions rendered by our Courts. He examines more particularly some of the first Charter decisions emanating from the Supreme Court of Canada. He writes that the Charter may have a damaging effect on labour law especially in relation to the right to strike and to picket. He concludes that the Charter is ill-suited for use in the labour relations domain.